A content and genre analysis of Black romance novels in South Africa - Mhlambi, Nolwazi (My University, 2023)
The popularity of independently published black women authors within the South African publishing market has raised multiple areas of interest. The project has both genre analysis and content-based goals. Firstly, these goals have to do with defining what is Black South African romance and identifying the literary narratives that fall within this genre. Secondly, the project analyses the identified themes as part of the literature review and as part of common themes such as gender-based violence, patriarchy, violence, and intimate partner violence that are identifiable in romance novels written by Black South African women. Consequently, these themes become a vehicle to interrogate why black romance novels are actively gatekept from mainstream publishing and how these challenges of gatekeeping present themselves to these authors.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts by Coursework to the Faculty of Humanities, School of Literature, Language and Media, University of the Witwatersrand, Johannesburg, 2023